Increasing Resource Parents’ Access to Training and Data: An Overview of Two Child Welfare Initiatives - Romano, Elisa; Stenason, Lauren (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2022)
Objectives: Resource parents are critical to young people’s well-being, resilient functioning, and placement stability. However, child welfare often experiences challenges in retaining resource parents, which may be partially due to the limited availability of in-service resources. We describe two in-service training initiatives for resource parents in Ontario (Canada) that can support their important caregiving work. We also present preliminary mixed-methods findings on training reactions and learning. Methods: The first study sampled 91 resource parents who completed the Resource Parent Curriculum (RPC) and collected module evaluations as well as post-program satisfaction data. The second study collected post-training evaluations from 26 resource parents who completed training using the Assessment and Action Record (AAR) to better understand youth in-care. Results: Resource parents responded positively to the RPC content and delivery; they appreciated the online format (due to COVID-19 restrictions). Parents noted it was helpful to learn how trauma shapes young people’s expectations and how thoughts, feelings, and behaviours are interconnected. For the second study, parents’ overall training rating was positive. They noted it was helpful to learn how different perspectives could be integrated through AAR findings and highlighted the importance of collaboration with child welfare workers. The training initiatives were well-received and attested to resource parents’ motivation to keep improving their parenting practices. Findings indicated gains in knowledge around trauma-informed parenting and indicated the value of data to support young people’s well-being. Implications: Retention will likely improve when resource parents feel supported and capable of handling young people’s complex needs. To improve outcomes for both youth in-care and resource parents, it seems important to make training and support available on a regular and ongoing basis and in a collaborative way with child welfare partners.